Evaluation of the Relationship between the Concentration of Suspended Particles and the Levels of C-Reactive Protein in Blood Plasma (Case study of Zahedan) - Abdolali Khammari; Mohsen Dahghani Ghnataghestani; Hossein Kamani; Ebrahim Alijani (Mazandaran University of Medical Sciences, 2021)
Introduction and purpose: Epidemiological research pointed to an association between air pollution and increased mortality from cardiovascular complications. There is a relationship between the incidence of cardiovascular complications and increased levels of C-reactive protein (hs-CRP). The present study aimed to determine the relationship between particulate matter concentration (PM10) and C-reactive protein in healthy youth in Zahedan. Methods: This longitudinal study was performed from February 2016 to October 2017. The concentration of suspended particles (PM10) was measured by the environmental method once every 6 days and on all dusty days. Moreover, in different conditions of air pollution, the amount of C-reactive protein in the blood samples of 40 volunteers aged 18-30 years was measured by enzyme-linked immunosorbent assay. The relationship between biomarkers and different air pollution conditions was investigated using a t-test. Results: The minimum, mean, and maximum concentrations of suspended particles (PM10) were reported as 30.75±9.8, 187.5±183.44, 2366.75±936.38 micrograms per cubic meter, respectively. The lowest rate is in February and the highest in August. Moreover, the minimum, mean, and maximum concentrations of C-reactive protein were obtained at 12±.96, 3.88±1.69, 9.95±2.39 μg/ml, respectively. Plasma C-reactive protein levels in air pollution conditions were significantly higher than those obtained in normal conditions (P<0.05). Conclusion: As evidenced by the obtained results, there was a direct relationship between the dust storm and C-reactive protein. Since cardiovascular and respiratory diseases are exacerbated when the concentration of particulate matter is above the standard, health programs and individual care need to receive assiduous attention.